2011
DOI: 10.1177/0954406211412154
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of unsteady tip clearance flow in an isolated axial compressor rotor blades row

Abstract: Three-dimensional unsteady numerical simulations were carried out to analyse tip clearance flow in a low-speed isolated axial compressor rotor blades row. A flow solver has been used for the current study utilizing the large eddy simulation (LES) technique. Periodic tip leakage flow and its propagation trajectories were simulated in detail. A number of pseudo pressure transducers were imposed on the pressure side of the blade for detection of unsteady surface pressures to provide a calculation of tip leakage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Using l 2 criterion, the point located in the vortex region requires l 2 5 0. Many researchers [14][15][16] have used l 2 to detect the vortex structures.…”
Section: Fluctuating Tip Clearance Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Using l 2 criterion, the point located in the vortex region requires l 2 5 0. Many researchers [14][15][16] have used l 2 to detect the vortex structures.…”
Section: Fluctuating Tip Clearance Flowmentioning
confidence: 99%
“…Fluctuating tip clearance flow has been confirmed to be the most prominent unsteady features near the casing. [13][14][15] Thus, it is meaningful to explore the relationship between the fluctuating tip clearance flow and rotating instability.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 8 suggested that the strongest unsteadiness was located near 50% chord of the pressure surface in the tip region. Taghavi-Zenouz et al 9 suggested that the strongest unsteadiness occurred at the position where the TLF impinged on the pressure side of the adjacent blade. Li et al 10 established a relationship between the unsteady tip leakage flow (UTLF) and spike-type stall inception.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies use computational fluid dynamics (CFD) codes or numerical methods based on the Navier-Stokes equations to investigate the performance of hydrostatic journal bearings. [44][45][46][47][48][49][50][51] Moreover, the CFD can be applied to model liquid flow in complex geometries for which Reynolds equation is unsuited. In hybrid hydrostatic/hydrodynamic bearings, the velocity and pressure variations, the onset of turbulence at high speeds and the mixing of entrainment flow with injected fluid have all been analyzed using the CFD.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48][49] CFD has also been applied to model lubricant flow in the gap between adjacent pad bearings. 50 To date, many studies have used CFD codes in their work [51][52][53][54] The present work deals with the analysis of the three-dimensional flow behaviors of the circular recess of the hydrostatic rotary table. Confining to the realistic geometries of the hydrostatic rotary table and work conditions of low rotation speed, only incompressible steady flow is investigated (Re i < 1400, Re s < 74.6).…”
Section: Introductionmentioning
confidence: 99%